The Cultural Dimension of Catholic Liturgical Rites in Catholic Religious Education in the Context of the Objectives of the Education System in Italy - Kiciński, Andrzej; Annicchiarico, Vincenzo (Verbum Vitae, 2022)
This article aims to show the possibility of an academic approach to teaching the Catholic religion at school to the liturgical rites of the Catholic Church from a cultural perspective. Liturgical rites consist of numerous signs and symbols that refer to the human dimension, which seeks what is beautiful, true, and good. At all levels, one of the main objectives of Italian and European schools is to teach, educate, and raise responsible and upright citizens. Therefore, while contributing to the general formation of the human being at school, the teaching of Catholic religion also draws students closer, in cultural terms, to the great code, i.e., the liturgy of the Catholic Church. It is certainly a form of public and social communication. It is education in action. In this sense, for example, it could be a considerable and systematic cultural opportunity for Ukrainian students residing in Poland, a chance to learn the symbolic language of the Catholic liturgy in the perspective of reaching human maturity without fear of proselytism from the Catholic Church. This article in no way intends to diminish the intrinsic value of the liturgy in the life of the Church, understood as a celebration, proclamation, commemoration, promise, and moral call whose purpose is to transform or transfigure the person so that he/she is oriented toward the highest good, i.e., God, and able to live a life of mutual love